Cancer survivors present significantly lower long-term stability of orthodontic treatment: a prospective case–control study - Mitus-Kenig, Maria; Derwich, Marcin; Czochrowska, Ewa; Pawlowska, Elzbieta (European journal of orthodontics, 2021)
The aim of the study was to compare the stability of orthodontic treatment in cancer survivors who had been treated with cytotoxic drugs with a generally healthy control group. The study included 52 cancer survivors treated orthodontically and 52 healthy control subjects matched for age, gender, and malocclusion. The weighted Peer Assessment Rating (w-PAR) index, the Index of Complexity, Outcome and Need (ICON) were assessed before treatment, after the treatment, and at the 3-year follow-up. Patients Satisfaction Score was assessed after the treatment and at the 3-year follow-up. A repeated analysis of variance test was used to check the statistical significance between the scores. Ideal occlusion was achieved in all patients. The mean w-PAR and ICON values were significantly reduced in both groups after the end of the orthodontic treatment with no significant differences between the groups regarding the obtained results. However, after the 3-year follow-up, only the cancer survivors' group presented statistically significant (P < 0.001) increase of the w-PAR and ICON values comparing to the values obtained at the end of the treatment. There was no significant change in Patients' Satisfaction Score within 3 years after treatment. The limited size of the study sample as well as different types of oncological diagnoses could have had an impact on the final results of the study. Previous cytotoxic drug treatment significantly decreases the stability of orthodontic treatment among the cancer survivors, particularly within first 12 months after the end of the treatment.